Lactobacillus rhamnosus GG for Cow's Milk Allergy in Children: A Systematic Review and Meta-Analysis - Weifu Tan; Zhicong Zhou; Wei Li; Han Lu; Zemin Qiu (Frontiers Media S.A., 2021)
Objective: Cow's milk allergy (CMA) is a common allergic disease. Probiotics have been suggested as a treatment for CMA, with Lactobacillus rhamnosus GG (LGG) being one of the important predominant choices. Despite reports on this topic, the effectiveness of application in CMA remains to be firmly established.Methods: To assess the effects of LGG on CMA in children, the PubMed/Medline, Embase, Cochrane Library, and Web of Science databases were searched for studies on LGG in treatment of CMA, which were published in the English language.Results: Ten studies were finally included. Significantly higher tolerability rates favoring LGG over controls were observed [risk ratio (RR), 2.22; 95% confidence interval (CI), 1.86-2.66; I2 = 0.00; moderate-quality evidence]. There were no significant differences in SCORAD values favoring LGG over the placebo (mean difference, 1.41; 95% CI, −4.99-7.82; p = 0.67; very low-quality evidence), and LGG may have improved fecal occult blood (risk ratio, 0.36; 95% CI, 0.14-0.92; p = 0.03; low-quality evidence).Conclusion: We found that LGG may have moderate-quality evidence to promote oral tolerance in children with CMA and may facilitate recovery from intestinal symptoms. However, this finding must be treated with caution, and more gpowerful RCTs are needed to evaluate the most effective dose and treatment time for children with CMA.Registration number: CRD42021237221.